2017
DOI: 10.1097/sap.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Head and Neck Melanoma In Situ With Staged Contoured Marginal Excisions

Abstract: Staged marginal evaluation of melanoma in situ (MIS) is performed in order to avoid reconstruction on positive margins. Contoured marginal excision (CME) is an excision of a 2mm wide strip of normal-appearing skin taken 5mm from the visible tumor periphery. If positive, a new CME is excised; the tumor is resected once negative margins are confirmed. The purpose of this study is to report our experience using this technique for the treatment of head/neck MIS. Clinicopathological data were abstracted for all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…SE offers a superior alternative to conventional WLE with complete peripheral margin evaluation resulting in lower recurrence rates. 3 , 11 , 12 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SE offers a superior alternative to conventional WLE with complete peripheral margin evaluation resulting in lower recurrence rates. 3 , 11 , 12 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that SE with rushed permanent sections is superior in obtaining clearance and reduced recurrence rates when compared to conventional WLE since it allows for complete control of the peripheral excision margins. 3 , 11 , 12 , 13 , 14 Recurrence rates for LM after SE have been reported as 1.8% to 4%. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…6 Concerns about outcomes for melanomas in cosmetic or functionally important locations have led several surgical groups to selectively use alternative surgical strategies with more comprehensive margin assessment before reconstruction. [7][8][9][10][11][12] Comprehensive margin assessment surgery often uses en face tissue processing to visualize a greater percentage of the surgical margins 13 and may be performed with paraffin-embedded permanent sections 10,11 or with frozen sections, 7,9,12 as in Mohs surgery. Mohs surgery was used for 3.5% of all melanomas from 2003 and 2009 according to Surveillance, Epidemiology, and End Results (SEER) data.…”
mentioning
confidence: 99%
“…It is important to note that most guidelines recommend surgical margins but do not specify desirable pathological margins for the management of MIS. While obtaining large margins on the head and neck is often difficult, 20 surgical excision margins [8 mm are now generally advised for LM. 13,14 While it is often possible for experienced practitioners to identify single junctional melanocytes on frozen sections with standard H&E staining or with rapid immunostains during Mohs surgery or CCPDMA, it can be challenging to determine the nature and significance of single melanocytes without interpreting them in the context of the main part of the lesion or the sun damaged background and its associated solar melanocytosis.…”
Section: Discussionmentioning
confidence: 99%